Teknik Produksi Pembesaran Udang Vaname (Litopenaeus vannamei): Studi Kasus di PT. Dewi Laut Aquaculture Garut - Iskandar, Andri; Wandanu, Dias; Muslim, Muslim (Politeknik Negeri Sambas, 2022)
Pacific whiteleg shrimp is a cultivated commodity with the prospect of increasing market opportunities yearly. The increase in value is in line with the increasing need for pacific whiteleg shrimp consumption. The impact is an increase in state income in general. Pacific whiteleg shrimp cultivation activities have been carried out on a large and small scale. However, proper enlargement production techniques are needed to increase production. This study aims to determine the technique of pacific whiteleg grow-out so that the information obtained can be disseminated to the public and will add value to the benefits of improving welfare. A study case method with a descriptive analysis approach was used. Pacific whiteleg shrimp culture is divided into the hatchery and grow-out sectors. The grow-out activities include pond cleaning, media preparation, fry stocking, feeding, treatment, pest and disease management, growth sampling, and harvesting. Based on the study's results, the production consisted of three cycles per year with a density of 180 m2 an SR value of 85.5%, and an FCR value of 1.25%.